2011
DOI: 10.1002/eqe.1132
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of orthogonal horizontal ground motion components for specified earthquake and site characteristics

Abstract: SUMMARYA method for generating an ensemble of orthogonal horizontal ground motion components with correlated parameters for specified earthquake and site characteristics is presented. The method employs a parameterized stochastic model that is based on a time-modulated filtered white-noise process with the filter having time-varying characteristics. Whereas the input white-noise excitation describes the stochastic nature of the ground motion, the forms of the modulating function and the filter and their parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 30 publications
1
82
0
1
Order By: Relevance
“…The advantage of using the model in Equation is due to the fact that it preserves the realistic non‐Gaussian character of earthquakes, a feature usually not considered in other models. () The non‐Gaussianity of real earthquakes is supported by the results in Figure a, which show that the kurtosis coefficient as a function of v s 30 for the ground motions in the NGA‐West data set is greater than 3, the characteristic value for Gaussian processes. Figure b shows the probability distribution function of the kurtosis κ for the type‐C National Earthquake Hazard Reduction Program (NEHRP) soil, similar to the soil assumed for this study.…”
Section: Seismic Hazardmentioning
confidence: 69%
See 1 more Smart Citation
“…The advantage of using the model in Equation is due to the fact that it preserves the realistic non‐Gaussian character of earthquakes, a feature usually not considered in other models. () The non‐Gaussianity of real earthquakes is supported by the results in Figure a, which show that the kurtosis coefficient as a function of v s 30 for the ground motions in the NGA‐West data set is greater than 3, the characteristic value for Gaussian processes. Figure b shows the probability distribution function of the kurtosis κ for the type‐C National Earthquake Hazard Reduction Program (NEHRP) soil, similar to the soil assumed for this study.…”
Section: Seismic Hazardmentioning
confidence: 69%
“…() The limitations of scaling ground motions may be resolved by simulating synthetic ground motions, an approach that has already been adopted in the performance‐based seismic analysis of structures. ()…”
Section: Introductionmentioning
confidence: 99%
“…For the physicsbased method, we simulate the two horizontal components of velocity at the azimuths of the station components. For the stochastic site-based model, each pair of horizontal velocity records is differentiated to acceleration and rotated to the direction of two stochastically uncorrelated orthogonal components before simulation (i.e., the principal components as described in Rezaeian and Der Kiureghian, 2012 …”
Section: Databasementioning
confidence: 99%
“…This lower stress drop is used to explain the results of previous studies that the median response spectra from aftershocks are observed to be systematically 20% to 40% lower at short spectral periods than the median response spectra from main shocks. In this paper, we develop an aftershock synthetic ground motion model by extending to far‐field aftershocks the model proposed by Rezaeian and Der Kiureghian for far‐field main shocks . The proposed aftershock model is calibrated using aftershock ground motions from the Pacific Earthquake Engineering Research Center (PEER) NGA‐West2 ground motion database .…”
Section: Introductionmentioning
confidence: 99%